Woman’s career development in hotel sector in Edo State, Nigeria - Ebere, Ihemeje Josephine (2016)
The hotel sector has been said to offer large career opportunities and advancement for both men and women, having chains of departments and sections which employees can advance in their career. However, these career advancement opportunities in the hotel sector are very limited when it comes to women due to the preconceived assumption that women are less managerial oriented than men. The main purpose of this study is to examine factors influencing career development of women in the hotel sector in Etsako West Local Government Area of Edo State in Nigeria. This study examined the impact of six measures of micro and macro factor based on organizational culture, family factor, individual factor, socio-cultural factor, economic factor and technological change. A quantitative method was used in this study. The study sampled 460 women in 18 selected hotels in three major cities in Etsako West Local Government Area. Data were collected using survey questionnaire through convenient sampling technique and a self-administered questionnaire that was distributed to the respondents. Pearson Correlation analysis was applied to analyze the relationship between the dimensions of micro and factors and career development for women. The results on correlation have shown that all the dimensions of micro and macro factors have a positive and significant relationship with the career development of women in the hotel sector in Etsako West Local Government Area. The study also conducted a multiple regression analysis to analyze the dimensions of micro and macro factor that mostly predicts career development. The findings suggested that the six dimensions of micro and macro factor contribute positively and significant to the variation in the career development of women. In summary, the findings indicate that achieving career success in hotel sector among women need an innovative technological awareness program especially with those who have an interest in reaching the managerial level in the sector. This can be done by organizing on the job training capable of enhancing the technological competence of women staff. Likewise, it is suggested that the organizational culture should offer a supportive organization environment for career development and give equal opportunity between male and female as it is acknowledged that higher positions give access to better salaries. In conclusion, this study is significant to the hospitality industry management, the government, and human resources recruitment practitioners. The findings of this study should be able to educate policy makers in Nigerian hotel sector on how to improve and sustain women career development as well as assists the government to plan and formulate feasible and viable policies towards ensuring that a hotel operator in Nigeria maintains gender equality in their respective sector. It is also recommended that managers of hotel sector promote gender friendly organizational policies that could encourage professionalism and merit rather than discrimination that will encourage the career path of women.